ANALYSIS OF THE ORGANIZATION'S ACTIVITY ON THE EXAMPLE OF THE BCG MATRIX. THEORETICAL-EXPERIMENTAL APPROACH - Yeritsyan, Hovhannes (Bulletin of Yerevan University G: Economics, 2025)
More than four decades after Bruce Henderson introduced BCG's growth-share matrix, the concept retains its significance. Companies continue to need a disciplined approach to oversee their product portfolio, R&D investments, and business units. Harvard Business Review acknowledges it as one of the frameworks that have had a transformative impact globally, and it continues to hold a central role in strategy teachings in business schools. However, substantial changes have transpired since its inception in 1970. These include the decline of conglomerates, an acceleration in the pace of change, and a reduction in the longevity of competitive advantages. Despite these shifts in the business landscape, the BCG growth-share matrix remains relevant, adapting to the evolving environment through important enhancements. The matrix continues to be a valuable tool for businesses, offering insights into strategic decision-making and portfolio management in the face of contemporary challenges. Today, the matrix can be customized to facilitate strategic experimentation for success in unpredictable markets. This involves accelerating innovation, balancing investments between new and established businesses, disciplined decision-making for investments and divestments, and meticulous measurement and monitoring of experimentation. The author carried out an analysis of business activity using the BCG matrix, showing not only the theoretical-methodological foundations of the tool, but also their practical application.
Keywords: BСG mаtrix; mаrkеt grоwth rаtе; rеlаtivе mаrkеt shаrе; dоgs; quеstiоn mаrks; stаrs; саsh соws.